BASS: um arcabouço de software para integração de sistemas de informação: um arcabouço de software para integração de sistemas de informação - Mateus Conrad Barcellos da Costa (2008)
This thesis presents the software framework BASS: Business Application Support through Software Services. BASS aims at supporting Information Systems Integration. BASS development originated from our investigation about the interplay between requirements and technology in the Information Systems Integration domain. Such development encompassed a technological dimension (the BASS framework) and a Software Process dimension, with the definition of process elements needed for the effective use of the framework. Amongst the benefits achieved with BASS are the simplification of how to deal with complex technologies and the reduction of design and implementation efforts in the development of Information Systems Integration software solutions.